Breaking the Delay: Stage III HIV Diagnosis and Successful Recovery at the Primary Healthcare Level - Sahika Nisandi Ayudelvi; Ronald Pratama Adiwinoto; Diadema Dicky Fansia; Muzna Anisah; Khakan Baguna; Iriyadi Iriyadi; Eltari Primasari (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Human Immunodeficiency Virus (HIV) remains a major public health problem, particularly when diagnosis occurs at an advanced stage. This case report describes a 24-year-old male diagnosed with WHO stage III HIV infection at a primary health care facility in the absence of CD4 count and baseline viral load due to resource limitations. The patient presented with oral candidiasis, chronic diarrhea, prolonged fever, and significant weight loss, alongside high-risk sexual behavior. HIV and syphilis serology were reactive, while tuberculosis was excluded despite strong clinical suspicion. The patient was managed with antifungal therapy, syphilis treatment, and first-line antiretroviral therapy (ART). Significant clinical improvement was observed within one month, and viral load decreased to 60 copies/mL at six months, indicating near-complete virological suppression. This case highlights missed opportunities for early HIV diagnosis, supports the use of WHO clinical staging as a surrogate in resource-limited settings, and demonstrates that effective HIV management can be achieved at the primary care level.